Digital Control of Variable Frequency Interleaved DC-DC Converter - Kroics, Kaspars (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This paper represents a design and implementation of a digital control of variable frequency interleaved DC-DC converter using a digital signal processor (DSP). The digital PWM generation, current and voltage sensing, user interface and the new period and pulse width value calculation with DSP STM32F407VGT6 are considered. Typically, the multiphase interleaved DC - DC converters require a current control loop in each phase to avoid imbalanced current between phases. This increases system costs and control complexity. In this paper the converter which operates in discontinuous conduction mode is designed in order to reduce costs and remove the current control loop in each phase. High current ripples associated with this mode operation are then alleviated by interleaving. Pulse width modulation (PWM) is one of the most conventional modulation techniques for switching DC - DC converters. It compares the error signal with the sawtooth wave to generate the control pulse. This paper shows how six PWM signals phase-shifted by 60 degrees can be generated from calculated values. To ensure that the measured values do not contain disturbances and in order to improve the system stability the digital signal is filtered. The analog to digital converter's (ADC) sampling time must not coincide with the power transistor's switching time, therefore the sampling time must be calculated correctly as well. Digital control of the DC-DC converter makes it easy and quickly to configure. It is possible for this device to communicate with other devices in a simple way, to realize data input by using buttons and keyboard, and to display information on LED, LCD displays, etc.